Role of resistance training for preventing frailty and metabolic syndromes in aged adults - Masahiko Yanagita; Yoko Shiotsu (Japanese Society of Physical Fitness and Sports Medicine, 2014)
In subjects with frailty syndrome, aging-related loss of muscle (sarcopenia) might progress to the extent that an older person loses his or her ability to live independently. Metabolic syndrome is a set of risk factors (abdominal obesity, insulin resistance, hypertension, and dyslipidemia) which markedly increases the risk of arteriosclerotic vascular disease. Due to the ongoing obesity pandemic and growing elderly population, frailty and metabolic syndromes are major emerging concerns in the healthcare system. Recent studies show that resistance training has remarkable beneficial effects on the musculoskeletal system including the prevention and treatment of these syndromes. Resistance training is probably the most effective measure to prevent and treat sarcopenia. With regard to the effect of resistance training on the muscular strength of elderly persons, the rate of improvement increases with intensity. Resistance training also has a favorable effect on metabolic syndrome since it decreases fat mass including abdominal fat, enhances insulin sensitivity, improves glucose tolerance, and reduces blood pressure values. Optimal nutrition enhances the anabolic effect of resistance training. Resistance training should be a central component of public health promotion programs along with aerobic exercise.